The protective effects of yellow tea extract against loperamide-induced constipation in mice. Issue 12 (21st May 2021) - Cao, Pei-Qin; Li, Xiu-Ping; Ou-Yang, Jian; Jiang, Rong-Gang; Huang, Fang-Fang; Wen, Bei-Bei; Zhang, Xiang-Na; Huang, Jian-An; Liu, Zhong-Hua
Abstract : We evaluated the effects of yellow tea extract on relieving constipation induced by loperamide and evaluated the changes of gut microbiota based on 16S rRNA gene sequencing. Abstract : Yellow tea, a rare type tea from China, has a rich breadth of functional ingredients and benefits the gastrointestinal tract. However, it is not clear whether the yellow tea extract can alleviate constipation. Therefore, we used loperamide-induced constipation in mice to evaluate the effects of yellow tea extract. Fifty Kunming mice were randomly divided into five groups: normal, model, low-dose yellow tea extract, low-dose yellow tea extract prevention group, and high-dose yellow tea extract prevention group. Mice were administered yellow tea extract for 5 weeks followed by loperamide-induced constipation for the final 2 weeks. The results showed that yellow tea extract alleviated constipation symptoms by improving the fecal water content, defecation weight, and gastrointestinal transit rate. Yellow tea extract intervention also protected colon tissue, regulated serum neurotransmitters, and decreased the vasoactive intestinal peptide level. Furthermore, qRT-PCR indicated that yellow tea extract regulated genes associated with the constipation state, raised 5-HT3 and 5-HT4 and reduced AQP3 and AQP4 mRNA expression. Moreover, we found that yellow tea extract changed the gut microbiota composition. Community diversity and richness were increased and principal co-ordinate analysis demonstrated that the yellow tea extract prophylaxis groups differed from the model group. Difference analysis indicated that yellow tea extract increased Roseburia, Lachnospiraceae_UCG-006, and Bifidobacterium and decreased norank_f_Clostridiales_vadinBB60_group, unclassified_o_Bacteroidales, and Bacteroides, which are correlated with constipation. Based on these results, we believe that regular yellow tea consumption can effectively alleviate constipation.